Friction aided deep drawing of sheet metals using polyurethane ring and auxiliary metal punch. Part 1: experimental observations on the deep drawing of aluminium thin sheets and foils - Hassan, M.A.; Takakura, N.; Yamaguchi, K. (2002)
Friction aided deep drawing based on the Maslennikov process is investigated as a method to facilitate the deep drawing of sheet metals with poor drawability. Aluminium foils and thin sheets of 0.1-0.4 nun in thickness are used as a model for the material with poor drawability. An auxiliary metal punch is used together with a polyurethane ring to increase the drawing efficiency and to improve the dimensional accuracy of the drawn cup. The effect of drawing conditions such as thickness, hole diameter and the hardness of the polyurethane ring on the cup height are mainly investigated. Also, the optimum number of drawing operations required to achieve a given drawing ratio is examined by repeating compression and unloading the polyurethane ring. The experimental results show that even for foil and thin sheets, deep cups with drawing ratios of 2.25 and with good shape and dimensional accuracy can be obtained by repeating the drawing operation about ten times. The achievable drawing ratio is appreciably larger when compared with that obtained by the conventional deep drawing process. (C) 2002 Elsevier Science Ltd. All rights reserved.